2011
DOI: 10.1002/da.20837
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the psychometric properties of the PTSD checklist (PCL) military, civilian, and specific versions

Abstract: The Posttraumatic Stress Disorder Checklist is a commonly used measure, with military (PCL-M), civilian (PCL-C), and specific trauma (PCL-S) versions. This synthesis of the psychometric properties of all three versions found the PCL to be a well-validated measure. The PCL shows good temporal stability, internal consistency, test-retest reliability, and convergent validity. The majority of structural validity studies support four factor models. Little is available on discriminant validity and sensitivity to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
620
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 862 publications
(648 citation statements)
references
References 66 publications
17
620
0
11
Order By: Relevance
“…It is one of the most frequently used self-report questionnaires for PTSD. Previous versions were extensively validated (McDonald & Calhoun, 2010; Wilkins, Lang, & Norman, 2011). The PCL-5 measures the 20 DSM-5 PTSD symptoms over the last week, rated on a 5-point Likert scale, ranging from 0 ( not at all ) to 4 ( extremely ).…”
Section: Methodsmentioning
confidence: 99%
“…It is one of the most frequently used self-report questionnaires for PTSD. Previous versions were extensively validated (McDonald & Calhoun, 2010; Wilkins, Lang, & Norman, 2011). The PCL-5 measures the 20 DSM-5 PTSD symptoms over the last week, rated on a 5-point Likert scale, ranging from 0 ( not at all ) to 4 ( extremely ).…”
Section: Methodsmentioning
confidence: 99%
“…Adkins et al [7] showed that the PCL was the strongest in discriminating PTSD from depression, social phobia and anxiety when compared to six other self-report measures of PTSD. On the other hand, there seems to be a considerable variability in cut-off scores due to the characteristics of sample to which the measure was administered [8].…”
Section: Introductionmentioning
confidence: 99%
“…For the previous version, three versions exist and differ in wording with respect to the anchored event (PCL-Military, PCL-Civilian and PCL-Specific). In a systematic review of the PCLrelated psychometric studies, Wilkins et al [8] suggested that the measure (particularly PCL-Specific) has exhibited sound psychometric properties. Likewise, the expanded version prompts participants to identify a specific traumatic event at the outset of the measure, and thus PCL-5 can be used for assessment of PTSD in all types of traumatic experiences.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to screening, widely used self-report measures such as the PTSD Checklist (PCL; Weathers, Litz, Herman, Huska, & Keane, 1993) and the Impact of Event Scale-Revised (IES-R; Weiss, 2004) have been evaluated in clinical and military settings whereas less is known of their properties in the context of disasters (for reviews, see Brewin, 2005;McDonald & Calhoun, 2010;Wilkins, Lang, & Norman, 2011). In addition, several studies have used other self-report measures as the reference standard (e.g., Creamer, Bell, & Failla, 2003;Olde, Kleber, van der Hart, & Pop, 2006), which seem to inflate the screening accuracy as compared to studies that use a structured clinical interview as reference (Beck et al, 2008).…”
Section: Introductionmentioning
confidence: 99%